In vitro immunomodulatory activity test of Bengle rhizoma extract (Zingiber cassumunar Roxb.): phagocytic activity of macrophages and lymphocyte proliferation in mice - Ghina Adhila; Nurkhasanah Nurkhasanah; Nanik Sulistyani (Pharmaciana, 2019)
Immunomodulators are pharmacological agents that affect the immune system at different levels. Aside from modulating, some immunomodulators stimulate, while some others inhibit immune responses. Zingiber cassumunar Roxb. or Bengle rhizoma has been reported to exhibit immunomodulatory activities. This research was intended to determine the pharmacological effects of its extract on the phagocytic activity of macrophages and lymphocyte proliferation in vitro. It used the macrophages and lymphocytes of male BALB/c mice, which were divided into normal control and treatment group (receiving 25, 50, and 100 ppm of extract). The immunomodulatory activity test results showed that 100 ppm of Bengle rhizoma extract reduced phagocytosis in macrophages much significantly than the control group and that the treatment groups suppressed the proliferation of lymphocytes more substantially than the control group. The extract decreased the phagocytic activity of macrophages and the proliferation capacity of lymphocytes when administered at a concentration of 100 ppm.